Solid Objects : Modernism and the Test of Production - Mao, Douglas (Book collections on Project MUSE., 2001)
In this provocative and wide-ranging study, Douglas Mao argues that a profound tension between veneration of human production and anxiety about production's dangers lay at the heart of literary modernism. Focusing on the work of Virginia Woolf, Wyndham Lewis, Ezra Pound, and Wallace Stevens, Mao shows that modernists were captivated by physical objects, which, regarded as objects, seemed to partake of a utopian serenity beyond the reach of human ideological conflicts. Under a variety of historical pressures, Mao observes, these writers came to revere the making of such things, and especially t.